2018
DOI: 10.3390/genes9060293
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Acute Hepatitis B: New Insights in Its Natural History and Implications for Antiviral Treatment

Abstract: Acute hepatitis B infection (AHB) is still a common viral acute hepatitis worldwide. As vaccination, antiviral treatment, and immigration are bound to affect the epidemiological landscape of HBV infections, and some of its aspects need to be investigated: (1) the circulation of vaccine escape mutants and of primary drug resistant strains; (2) the change in HBV genotype prevalence; and (3) the clinical implications of AHB and the probability of chronification. The serological, virological, and clinical paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(47 reference statements)
0
7
0
1
Order By: Relevance
“…There are limited data on HBsAg clearance rates in HBV incident cases; however, a study in Rome reported an HBsAg clearance rate of about 82% in acute HBV patients. [ 27 ] According to our knowledge, in Botswana, HBsAg clearance has only been reported for chronic HBV patients where 37% of participants on anti-HBV treatment (tenofovir and emtricitabine) over a 2-year period cleared HBsAg. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data on HBsAg clearance rates in HBV incident cases; however, a study in Rome reported an HBsAg clearance rate of about 82% in acute HBV patients. [ 27 ] According to our knowledge, in Botswana, HBsAg clearance has only been reported for chronic HBV patients where 37% of participants on anti-HBV treatment (tenofovir and emtricitabine) over a 2-year period cleared HBsAg. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, AHB is of clinical concern as it most often requires hospital admission sometimes being a threat to the patient's life. It was related to strains from elsewhere, [ 27 ] and this raised concern of treatment of immigrants. Furthermore, Jindal et al [ 46 ] state that reactivation of HBV is associated with immunosuppression and will most often present as AHB, hence the need to further assess predictors of chronicity in these patients, particularly because they are coinfected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Although an aggressive cytotoxic response seems to be required for rapid HBsAg clearance, with the drawback of a more intense (albeit transient) parenchymal damage, here we observed rapid HBsAg loss associated with a favourable outcome (no liver injury). Menzo et al indicate that both HBsAg at day 28 and the kinetics of HBsAg in the first four weeks from admission are predictors of the chance of clearing HBsAg within six months (Menzo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The previously comparative study (Han et al, 2014) does not specifically mention HBV genotypes, while many studies have shown clinical and biological variations according to the HBV genotype (Revill et al, 2020). For instance, patients infected by genotype D would experience the highest liver alterations and the lowest HBsAg titres (Menzo et al, 2018), but the impact of genotype E has never been investigated. Further studies are needed to investigate the evolution of HBsAg titre according to genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Не дивлячись на досягнення медицини та постійне впровадження нових медичних технологій у практику з метою контролю над інфекційними процесами, вірусні гепатити є суттєвою причиною підвищення захворюваності та смертності [1][2][3][4]. На сьогодні у світі 1 млрд інфікованих та 350 млн чоловік носіїв вірусу ГВ, які є постійним резервуаром та джерелом інфекції [5].…”
Section: вступunclassified